Nonlinear Dirac equation in Bose-Einstein condensates: preparation and stability of relativistic vortices - Haddad, Laith H.; O'Hara, Kenneth M.; Carr, Lincoln D. (Physical review. A, Atomic, molecular, and optical physics, 2015)
We propose a detailed experimental procedure for preparing relativistic vortices, governed by the nonlinear Dirac equation, in a two-dimensional Bose-Einstein condensate (BEC) in a honeycomb optical lattice. Our setup contains Dirac points, in direct analogy to graphene. We determine a range of practical values for all relevant physical parameters needed to realize relativistic vortices in a BEC of 87Rb atoms. Seven distinct vortex types, including Anderson-Toulouse and Mermin-Ho skyrmion textures and half-quantum vortices, are obtained, and their discrete spectra and stability properties are calculated in a weak harmonic trap. We predict that most vortices are stable, with a lifetime between 1 and 10 s.
Gesehen am 03.03.2021